Development of Alveolar Hemorrhage After Pfizer-BioNTech COVID-19 mRNA Vaccination in a Patient With Renal-Limited Anti-neutrophil Cytoplasmic Antibody-Associated Vasculitis: A Case Report - Nishioka, Ken; Yamaguchi, Shintaro; Yasuda, Itaru; Yoshimoto, Norifumi; Kojima, Daiki; Kaneko, Kenji; Aso, Mitsuhiro; Nagasaka, Tomoki; Yoshida, Eriko; Uchiyama, Kiyotaka; Tajima, Takaya; Yoshino, Jun; et al. (Frontiers in Medicine, 2022)
Since the coronavirus disease 2019 (COVID-19) pandemic continues and a new variant of the virus has emerged, the COVID-19 vaccination campaign has progressed. Rare but severe adverse outcomes of COVID-19 vaccination such as anaphylaxis and myocarditis have begun to be noticed. Of note, several cases of new-onset antineutrophil cytoplasmic antibody-associated vasculitis (AAV) after COVID-19 mRNA vaccination have been reported. However, relapse of AAV in remission has not been recognized enough as an adverse outcome of COVID-19 vaccination. We report, to our knowledge, a first case of renal-limited AAV in remission using every 6-month rituximab administration that relapsed with pulmonary hemorrhage, but not glomerulonephritis, following the first dose of the Pfizer-BioNTech COVID-19 vaccine. The patient received the COVID-19 vaccine more than six months after the last dose of rituximab according to the recommendations. However, his CD19+ B cell counts were found to be increased after admission, indicating that our case might have been prone to relapse after COVID-19 vaccination. Although our case cannot establish causality between AAV relapse and COVID-19 mRNA vaccination, a high level of clinical vigilance for relapse of AAV especially in patients undergoing rituximab maintenance therapy following COVID-19 vaccination should be maintained. Furthermore, elapsed time between rituximab administration and COVID-19 mRNA vaccination should be carefully adjusted based on AAV disease-activity.